Anatomical and histochemical aspects of the peach palm (Bactris gasipaes Kunth) seed - Nazário, Patrícia; Ferreira, Sidney Alberto do Nascimento; Borges, Eduardo Euclydes de Lima e; Genovese-Marcomini, Poliana Roverse; Mendonça, Maria Silvia de (Journal of Seed Science, 2013)
Bactris gasipaes Kunth (peach palm) is a palm tree (Arecaceae) widely used by Amazon people, whose seeds have dormancy of unknown cause, which result in difficulties on producing uniform seedlings. This study aimed at identifying anatomical and histochemical aspects of peach palm seeds that may have influence on germination. Histological sections were performed with seed material embedded into hystoresin, which were then stained with toluidine blue and assessed under optical microscope to verify structural characteristics. Histological sections were manually performed to identify primary and secondary metabolites; and histochemical test were performed for fatty acids, alkaloids, starch, phenolic compounds, lignin, neutral and acidic lipids, pectins, polysaccharides, proteins, tannins, and terpenoids. Tegument is thin and contains two layers. The external layer is thicker and has vascular bundles; and the internal layer is thinner containing irregular cells replete of phenolic compounds. Endosperm is whitish in color, with cells with shapes that vary from oblong or ellipsoidal until oval; containing lipids, proteins, pectins, and polysaccharides. Embryo is relatively small as related to seed size, conical and vascularized at distal portion. On longitudinal sections, plumule appears in proximal region as three foliar primordia. At seedling protrusion region the cells contain acidic lipids, proteins, and neutral polysaccharides.
Aspectos anatômicos e histoquímicos da semente de pupunha (Bactris gasipaes Kunth)